HAK NAFKAH ISTRI DALAM RUMAH TANGGA NOMADEN PERSPEKTIF HUKUM KELUARGA KONTEMPORER - Alimuddin, Ahmad (El-Ahli : Jurnal Hukum Keluarga Islam, 2025)
This study examines the right of wives to receive financial support (nafkah) within nomadic households from the perspective of contemporary Islamic family law. The research aims to explore how Islamic principles can be flexibly applied to ensure the fulfillment of this right in dynamic social contexts. Using a qualitative approach, this study combines normative analysis—based on the Qur’an, Hadith, classical fiqh, and contemporary fatwas—with empirical fieldwork involving semi-structured interviews with ten Muslim couples living nomadic lifestyles in Jakarta, Surabaya, and Makassar. Findings reveal that while the obligation of husbands to provide nafkah remains central, nomadism creates challenges such as unstable income, high living costs, and disrupted emotional support. Nevertheless, families adopt adaptive strategies, including digital financial management, joint decision-making, and remote employment opportunities, to maintain stability. The normative-empirical integration demonstrates that sharia principles, when applied with contextual flexibility, can offer practical solutions for nomadic families. This study contributes to the discourse of Islamic family law by highlighting its responsiveness to contemporary socio-economic dynamics and recommends further research on rural contexts and policy advocacy to strengthen protections for wives’ rights.